Bacterial stress responses - Storz, Gisela; Hengge, Regine (Monograph, ASM Press., 2011)
The second edition of Bacterial Stress Responses incorporates and reviews the vast number of new findings that have greatly advanced the understanding of bacterial stress responses in the decade since the publication of the first edition. Readers will discover how this improved understanding not only enhances our knowledge of all cellular regulation at the molecular level, but also provides new ammunition in the fight against pathogens and helps optimize the use of bacteria in biotechnology.